2014
DOI: 10.1007/s12094-014-1193-7
|View full text |Cite
|
Sign up to set email alerts
|

New biological markers in the decision of treatment of head and neck cancer patients

Abstract: Head and neck squamous cell carcinoma is the sixth most common cancer type worldwide. Also the 5-year survival rate of less than 50 % seems to be lower than other cancer types. There are some reasons behind this high mortality rate; one of them is the lack of knowledge about the biology and genomic instability behind the carcinogenic processes. These biological features could condition the failure of frontline treatment, in which case rescue treatment should be used, representing an overtreatment for the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…We divided patients into terciles based on RQ expression-low, medium, and high expression levels as in other similar studies 8 . The Kaplan-Meier method indicated that patients with high expression levels of the oncogenes miR-93-5p and miR-210-3p had significantly worse survival rates than patients with low/medium expression levels (χ 2 (2) = 4.68, log-rank p = 0.03; χ 2 (2) = 4.53, log-rank p = 0.03, respectively) (Fig. 4a,c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We divided patients into terciles based on RQ expression-low, medium, and high expression levels as in other similar studies 8 . The Kaplan-Meier method indicated that patients with high expression levels of the oncogenes miR-93-5p and miR-210-3p had significantly worse survival rates than patients with low/medium expression levels (χ 2 (2) = 4.68, log-rank p = 0.03; χ 2 (2) = 4.53, log-rank p = 0.03, respectively) (Fig. 4a,c).…”
Section: Resultsmentioning
confidence: 99%
“…Head and neck cancer and laryngeal carcinoma in particular is still a worldwide burden that has shown no significant improvement during the last few decades regarding definitive treatment strategies and earlier diagnosis. Despite recent advances in biological therapy, the survival rate still does not differ from the results achieved decades ago, and curative treatment options remain limited to surgery and/or chemoradiation therapy based on anatomic location and TNM staging 1 , 2 . The lack of suitable biomarkers in this field ensue failure in defining subgroups eligible for more individualized treatment protocols, something that has already been established in clinical practice for many other solitary malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the TNM grading does not reflect the considerable biological diversity of these tumours (5). Numerous studies on potential prognostic markers to foresee the outcome and therapeutic needs of individual OSCC patients have been performed (6)(7)(8). Despite concerted efforts, none of these biomarkers are routinely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Among several examples, MVP (major vault protein), IGF-1R (insulin-like growth factor 1 receptor), and BCL2 (B cell lymphoma 2) expression in tumor tissues have been suggested as useful biomarkers for an optimal planning of therapeutic strategy (Valenciano, 2014). Furthermore Foxp3 (forkhead/winged helix transcription factor p3) and TLR4 (toll-like receptor 4) could play a role in promoting the immune escape of CC suggesting a potential rational for new immunotherapeutic strategies (Zhang, 2017).…”
Section: Discussionmentioning
confidence: 99%